Modification of Sweet Potato Flour Production Facility Layout at Farmers Group United of Sukoanyar Village of Pakis District - Putri, Shyntia Atica; Agustin, Wike; Ikasari, Dhita Morita; Lutfian, Rizky; Sari, Rheysa Permata (Jurnal Teknologi Pertanian, 2014)
Sweet potato are one of agricultural commodity that can be used for processing product that have an added value. ‘Gapoktan Pakis’ are one of institution that carried out sweet potato processing. Discontinuity of production process are caused by poor layout where equipments and facility are put not in the place they should be placed. Other aspects that caused production discontinuity are impermanent production area since it is personal house. This research objective are to modify layout based on material flow and connection between facilities. The methods usedin the research are Operation Process Chart (OPC), Flow Process Chart (FPC), Activity Relationship Chart (ARC), and Activity Relationship Diagram (ARD). The results show that for production time of 265 minutes with production capacity of 10 kg produce 2.5 kg sweet potato flour. Facility layout that is suggested are product layout type and straight line material flow type.Keywords: product layout, straight line, sweet potato flour